Community‐based prenatal screening for postpartum depression in a South African township. Issue 1 (2nd April 2014) - Hung, Kristin J.; Tomlinson, Mark; le Roux, Ingrid M.; Dewing, Sarah; Chopra, Mickey; Tsai, Alexander C.
Abstract: Objective: To assess the feasibility of using community health workers to administer short or ultra‐short screening instruments during routine community‐based prenatal outreach for detecting probable depression at 12 weeks postpartum. Methods: During pregnancy and at 12 weeks postpartum, the 10‐item Edinburgh Postnatal Depression Scale (EPDS‐10) was administered to 249 Xhosa‐speaking black African women living in Khayelitsha, South Africa. We compared the operating characteristics of the prenatal EPDS‐10, as well as 4 short and ultra‐short subscales, with the criterion standard of probable postpartum depression. Results: Seventy‐nine (31.7%) women were assessed as having probable postpartum depression. A prenatal EPDS‐10 score of 13 or higher had 0.67 sensitivity and 0.67 specificity for detecting probable postpartum depression. Briefer subscales performed similarly. Conclusion: Community health workers successfully conducted community‐based screening for depression in a resource‐limited setting using short or ultra‐short screening instruments. However, overall feasibility was limited because prenatal screening failed to accurately predict probable depression during the postpartum period.